Exploring opportunities for government retirees to transfer their KSAOs for the national development : evidence from Malaysia / Khulida Kirana Yahya ... [et al.] - Yahya, Khulida Kirana; Johari, Johanim; Adnan, Zurina; Mohd Isa, Mohd Faizal; Daud, Zulkiflee (Research Management Institute (RMI), 2014)
The number of Malaysian senior citizens is expected to rise to 2.71 million by the year 2020. Malaysia will then become an ageing society, which includes the government retirees who have reached their mandatory retirement age of 60 years old. This study intends to examine knowledge, skills, abilities, and other characteristics (KSAOs) of the government retirees in Malaysia and to identify the opportunities for the retirees to transfer their KSAOs for the national development. To elicit findings, a total of 1,609 questionnaires were analyzed using SPSS version 16.0. The results indicated that most of the retirees had acquired vast KSAOs throughout their years of service, especially in the areas related to their tasks and responsibilities. It is therefore of paramount importance for the government and non-government bodies to develop appropriate means for these retirees to use their KSAOs. Several policy guidelines such as programs and activities can be undertaken by the relevant bodies to help government retirees optimize their KSAOs in a more meaningful way.